Inhaled nitric oxide. (16th November 2018) - Yu, Binglan; Ichinose, Fumito; Bloch, Donald B; Zapol, Warren M
Abstract : Nitric oxide (NO) is a gas that induces relaxation of smooth muscle cells in the vasculature. Because NO reacts with oxyhaemoglobin with high affinity, the gas is rapidly scavenged by oxyhaemoglobin in red blood cells and the vasodilating effects of inhaled NO are limited to ventilated regions in the lung. NO therefore has the unique ability to induce pulmonary vasodilatation specifically in the portions of the lung with adequate ventilation, thereby improving oxygenation of blood and decreasing intrapulmonary right to left shunting. Inhaled NO is used to treat a spectrum of cardiopulmonary conditions, including pulmonary hypertension in children and adults. However, the widespread use of inhaled NO is limited by logistical and financial barriers. We have designed, developed and tested a simple and economic NO generation device, which uses pulsed electrical discharges in air to produce therapeutic levels of NO that can be used for inhalation therapy. Linked Articles: This article is part of a themed section on Nitric Oxide 20 Years from the 1998 Nobel Prize. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.2/issuetoc